Light-quality and temperature-dependent CBF14 gene expression modulates freezing tolerance in cereals. (27th December 2015) - Novák, Aliz; Boldizsár, Ákos; Ádám, Éva; Kozma-Bognár, László; Majláth, Imre; Båga, Monica; Tóth, Balázs; Chibbar, Ravindra; Galiba, Gábor
Highlight: A low ratio of red to far-red light induces CBF14 gene expression and increases freezing tolerance via the action of phytochrome A and B photoreceptors in winter barley and bread wheat Abstract: C-repeat binding factor 14 (CBF14) is a plant transcription factor that regulates a set of cold-induced genes, contributing to enhanced frost tolerance during cold acclimation. Many CBF genes are induced by cool temperatures and regulated by day length and light quality, which affect the amount of accumulated freezing tolerance. Here we show that a low red to far-red ratio in white light enhances CBF14 expression and increases frost tolerance at 15°C in winter Triticum aesitivum and Hordeum vulgare genotypes, but not in T. monococcum (einkorn), which has a relatively low freezing tolerance. Low red to far-red ratio enhances the expression of PHYA in all three species, but induces PHYB expression only in einkorn. Based on our results, a model is proposed to illustrate the supposed positive effect of phytochrome A and the negative influence of phytochrome B on the enhancement of freezing tolerance in cereals in response to spectral changes of incident light. Key words: CBF-regulon, barley, cereals, cold acclimation, freezing tolerance, light regulation, low red/far-red ratio, phytochrome, wheat.